"Here I can just be myself": How youth and adults collaboratively develop an identity‐safe community across difference. Issue 5 (24th February 2021) - Rubin, Jennifer D.; Scanlon, Mike; Cechony, Anna; Chen, Katharine
Abstract: The aim of this study was to investigate the development of identity safety—where all participants are valued, included, and can engage without fear of stigmatization—among underrepresented youth and adults in a community‐based youth development program. Qualitative in‐depth interviews were conducted daily with three youth and two adult mentors about their experiences in the program (a total of 32 interviews). Data analysis revealed that participants developed identity safety through engaging in programmatic activities that explored youth's identities, practicing authenticity in daily interactions, and facilitating dynamic communication across intergenerational friendships. Participants described sustaining identity safety through formal social support spaces, mutual support in group settings, and peer support. Ultimately, these experiences set the foundation for youth and adults to engage in positive risk‐taking and self‐reflection. Implications for researchers and youth development programs are discussed.